ARABIC EVIDENCE FOR THE FORMATION OF THE VERBAL NOUN OF THE SEMITIC GT-STEM - Testen, David (Journal of Semitic studies, 1999)
DAVID TESTEN; ARABIC EVIDENCE FOR THE FORMATION OF THE VERBAL NOUN OF THE SEMITIC GT-STEM*, Journal of Semitic Studies, Volume XLIV, Issue 1, 1 March 1999, Page